Support Service for Military Personnel, Privates and Commanders of the Civil Defense Service, Police Officers and Members of Their Families as a Subject of Social Protection - Melnyk, K. Yu.; Tatarinov, R. V. (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article examines the state of legal regulation of the support services for military personnel, rank-and-file and senior civil defense personnel, police officers and members of their families. The points of view of scholars on the definition of the category of “social risk” are investigated. The legal status of the support service as a subject of social protection is studied. The author notes the shortcomings of the national legislation regulating the activities of support services for military personnel, rank-and-file and senior civilian protection officers, police officers and members of their families. In particular, the legal status of the head of the support service; the rights, duties and responsibilities of the support service; the algorithm of interaction of the support service with social protection authorities, health care institutions, embassies and consulates of foreign countries; the procedure for the activities of support services to provide support to military personnel, rank and file and senior officers of the civil protection service, police officers who have been injured (contusion, trauma, maim), diseases, as well as family members of the above-mentioned persons who went missing under special circumstances, were captured, or died while performing combat (special) missions are not enshrined. The necessity of developing a comprehensive regulatory legal act – the Regulation on Support Services for Military Personnel, Private and Commanding Officers of the Civil Protection Service, Police Officers and Members of Their Families – is substantiated. The following structure of this Regulation is proposed: section I “General provisions”, section II “Tasks and functions of the support service”, section III “Rights, duties and responsibilities of the head of the support service and the support person”, section IV “Procedure for the support service to provide support”, section V “Interaction of the support service with state authorities, local self-government bodies, embassies and consulates of foreign states”, section VI “Financial and logistical support of support services”, section VII “Control over the activities of support services”.